Ramadan fasting does not adversely affect neuromuscular performances and reaction times in trained karate athletes - Zarrouk, N.; Hammouda, O.; Latiri, I.; Adala, H.; Bouhlel, E.; Rebai, H.; Dogui, M. (Journal of the International Society of Sports Nutrition, 2016)
The present study aimed to investigate the concomitant effects of Ramadan intermittent fast (RIF) and muscle fatigue on neuromuscular performances and reaction times in young trained athletes.